Hubungan Kualitas Tidur dengan Derajat Keparahan Acne Vulgaris pada Siswa-Siswi Kelas X di Sma Muhammadiyah 2 Bandar Lampung Provinsi Lampung Tahun 2024 - Yeti Arian Desta; Sandra Andini; Budi Antoro (MES Bogor, 2024)
Acne vulgaris is a multifactorial chronic skin condition, characterized by inflammation in the pilosebaceous units, such as the formation of comedones, papules, pustules, nodules, and cysts, which typically present on the face, upper body, and upper arms. Sleep quality is defined by an individual's capacity to sleep adequately and achieve the necessary amount of rest. This study aims to identify the correlation between sleep quality and the severity of acne vulgaris among tenth grade students at Muhammadiyah 2 Senior High School of Bandar Lampung, Lampung Province in 2024.The research adopts a quantitative approach and analytical survey method with a cross-sectional design. The study population includes all 285 tenth-grade students at Muhammadiyah 2 Senior High School of Bandar Lampung, Lampung Province in 2024. A total of 74 respondents were selected using the Slovin formula based on inclusion and exclusion criteria, with a purposive sampling technique. The data were collected using the Pittsburgh Sleep Quality Index (PSQI) questionnaire and observations of the severity of acne vulgaris. Data analysis was conducted using univariate and bivariate analyses with the non-parametric chi- square test, utilizing SPSS version 26.The study revealed that 50 respondents (67.6%) had poor sleep quality, while 24 respondents (32.4%) experienced a moderate severity of acne vulgaris. The analysis indicates a significant correlation between sleep quality and the severity of acne vulgaris among tenth-grade students at Muhammadiyah 2 Senior High School in Bandar Lampung, Lampung Province in 2024, with a p-value of 0.000 ≤ 0.05. The results of this research provide useful information and may serve as a supplementary resource for future research.